Iowa Birdline update, September 7, 1992 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1992)
Email for the Iowa Birdline update for September 7, 1992. Highlights of the update include sightings of a King Rail, Red-necked Phalarope, Mississippi Kite, Black-throated Blue Warbler and a Sandhill Crane. Epson - sheet feed/flatbed